Kajian rencana pembuatan kerangka mesin pemecah kemiri desa siboruan kecamatan Balige kabupaten Toba provinsi Sumatera Utara - Siahaan, Saloom Hilton; Purba, Jhon Sufriadi; Simanjuntak, Mario Geraldi; Situmorang, Regi Chandela (Papanda Publisher, 2025)
Candles (Aleurites moluccana) have numerous benefits for human life. This is evident in Siboruon Village, Balige District, Toba Regency, North Sumatra Province. Candlenuts are a major agricultural commodity and are quite abundant during the harvest season. Post-harvest candlenut processing is still relatively conventional, often done manually by directly pounding the candlenuts, resulting in less than optimal production capacity. Therefore, researchers will conduct a design that will facilitate the cracking of candlenut shells. The authors used experimental research, constructing tools and conducting direct testing on objects in Siboruon Village, Balige District, Toba Regency, North Sumatra Province, from January to December 2024. The main frame of the candlenut shell cracking machine was designed using ST 37 angled steel with an